The Effect of Loneliness on Work Engagement among Chinese Seafarers: Mediating Effects of Executive Functions - Xinjie Qi; Daoke Li; Rong Lian (Behavioral Sciences)
In order to explore the effect of loneliness on work engagement and the role of executive function in Chinese seafarers, two studies were carried out. Study 1 conducted a questionnaire survey of 1231 active Chinese seafarers to examine the relationship between seafarers’ loneliness, work engagement, and executive functions. Study 2 involved 177 seafarers as participants and created scenarios of seafarer work loneliness and non-loneliness using a recall paradigm, measuring components of executive function such as inhibitory control, working memory, and cognitive flexibility, as well as willingness to engage in work. The findings indicate that seafarers’ sense of loneliness can significantly negatively predict their work engagement, with inhibition control, working memory, and cognitive flexibility playing mediating roles. This provides new references and insights for alleviating the negative impact of loneliness on seafarers and enhancing their work engagement through cognitive approaches.